PERTANGGUNGJAWABAN PIHAK BANK DALAM KASUS KEBOCORAN DATA PRIBADI YANG MENGAKIBATKAN KERUGIAN BAGI NASABAH - Rahayu Sulistyaningsih; Diana Tantri Cahyaningsih (Fakultas Hukum Universitas Sebelas Maret, 2026)
This article examines the liability of the bank in cases of personal data leakage that results in losses for customers. This research uses normative legal research. The research approach used is the Legislative Approach and the conceptual approach. The types and sources of legal materials used are primary legal materials and secondary legal materials. The technique of collecting legal materials used is the study of documents or library materials. The technique of analyzing legal materials uses the deduction method. The results of research and discussion show that the implementation of Personal Data Protection in banking activities until now there is no regulation that codifies it into one law and Leakage of personal data poses various risks including information being stolen and then sold to the Darkweb so that customers are worried about legal uncertainty regarding legal protection. of his personal data and the current regulation that describes the protection of personal data is still sectoral and partial. The form of bank accountability for cases of personal data leakage by replacing customer losses and Banks need to apply legal protection to customer personal data based on Bank Indonesia Regulation Number 7/6/PBI/2005 concerning product transparency, especially internet banking services by providing correct and honest information to customers.